Catatan perjalanan seni Zurinah Hassan : penerima anugerah penulisan S.E.A 2004 - Zurinah Hassan, 1949- (Kuala Lumpur : Institut Terjemahan dan Buku Malaysia, 2013)
Biography of Zurinah Hassan, a Malaysian writer and criticism of her writings.
Includes bibliographical references (page [143]-146).
Keywords: Zurinah Hassan, -- 1949-; Authors, Malay -- Biography